2003
DOI: 10.1007/bf02705477
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous scattering factors of some rare earth elements evaluated using photon interaction cross-sections

Abstract: The real and imaginary parts, f ¼´E µ and f ¼¼´E µ of the dispersion corrections to the forward Rayleigh scattering amplitude (also called anomalous scattering factors) for the elements La, Ce, Pr, Nd, Sm, Gd, Dy, Ho and Er, have been determined by a numerical evaluation of the dispersion integral that relates them through the optical theorem to the photoeffect cross-sections. The photoeffect cross-sections are derived from the total attenuation cross-section data set experimentally determined using high resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…The intensities of X-rays available from such sources also are comparatively low for scattering studies and photoelectric measurements, though they may be sufficient for attenuation measurements. The investigations by Ramachandran et al [6], Appaji Gowda et al [7,8], Budak et al [9], Tajuddin et al [10] are typical examples of the use of this method.…”
Section: Introductionmentioning
confidence: 97%
“…The intensities of X-rays available from such sources also are comparatively low for scattering studies and photoelectric measurements, though they may be sufficient for attenuation measurements. The investigations by Ramachandran et al [6], Appaji Gowda et al [7,8], Budak et al [9], Tajuddin et al [10] are typical examples of the use of this method.…”
Section: Introductionmentioning
confidence: 97%
“…Similarly, several investigators have experimentally determined atomic form factors for various elements at various energies [25][26][27][28][29][30][31][32][33][34][35][36]. Normally, two methods are adopted for measuring the form factors, namely the direct method and the attenuation method.…”
Section: Introductionmentioning
confidence: 99%
“…Normally, two methods are adopted for measuring the form factors, namely the direct method and the attenuation method. The direct method is based on (a) measurement of reflection and refraction [25,26], (b) determination of the intensities of the Bragg reflected rays [27,28] and (c) x-ray interferometry [29,30], However, the measurement of atomic form factors using the attenuation method is more reliable [31][32][33][34][35][36] and does not suffer from the problems associated with the other methods. The other advantage of the attenuation method is that the atomic form factors can be determined for a laiger range of atomic numbers over a wider range of x-ray or gamma-ray energies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The attenuation coefficient method can also be used to obtain the dispersion corrections f 0 and f 00 . Sandiago et al, 14 Umesh et al 5 and Appaji Gowda et al 15 have evaluated dispersion corrections around the K-shell for the elements Cu, Ag, Zr, Sn, La, Ce, Pr, Nd, Sm, Gd, Dy, Ho and Er, in the energy range 5-84 keV using the attenuation coefficient method. Drier et al 16 have reported results for Ni, Cu, Zn and Zr around the K-edge and for Ta, W, Pt and Au around the respective L-edges.…”
Section: Introductionmentioning
confidence: 99%